Development of a methodology for the evaluation of active safety using the example of preventive pedestrian protection : doctoral thesis accepted by Technische Universität Berlin, Germany /: doctoral thesis accepted by Technische Universität Berlin, Germany. ([2014]) - Helmer, Thomas
No abstract available